Tuberous sclerosis complex in a child: diagnosis and management - Prastiya Indra Gunawan; Aminuddin Harahap; Darto Saharso (Indonesian Pediatric Society, 2010)
Tuberous sclerosis complex (TSC) is a multisystem, autosomal dominant disorder affecting children and adults, resulted from mutations in one of two genes, TSC1 (encoding hamartin) or TSC2 (encoding tuberin) genes located on chromosomes 9 and 16 respectively.1,2 Synonyms of TSC are Bourneville Pringle syndrome, epiloia, or tuberosclerosis. This disorder is characterized by seizures, mental disability, and small noncancerous tumors on the skin and other body tissues, such as brain, eye, lung, and kidney. The classic triad are seizures, mental retardation, and cutaneous angiofibromas.3